THE ROLE OF THE NURSE IN DIAGNOSTIC AND THERAPEUTIC PROCEDURES IN ALLERGOLOGY - Maja Čamernik; Dolores Pivk; Monika Tomazin; Mateja Hren (The Society for Children with Metabolic Disorders, 2021)
In the last few years, there has been a significant increase in allergic conditions, probably due to changes in lifestyle and the natural environment. According to European data, over 30% of the population has allergies. These symptoms usually begin in early childhood and adolescence. Over the years, most allergies are alleviated or even disappear, but others last throughout adulthood or are lifelong. Allergy symptoms and signs present as allergic rhinitis and conjunctivitis, asthma, urticaria, allergy to insect venom (bites) and food allergies and drug hypersensitivity. In addition, they can occur as severe systemic allergic reactions - anaphylaxis. Together with the increased frequency of allergies, clinical allergology has also successfully developed. Modern diagnostic and therapeutic methods are available. In both segments, the nurse plays a significant role as a member of a multidisciplinary team. The nurse is actively involved in allergy diagnostics and treatment, and recently in research and the implementation of innovations in the management of allergic disease. Nursing roles within allergology reflect the complex care of patients with allergic conditions. They include performing assigned diagnostic procedures and treatment, ordered by the doctor, patient health education, care of patients with chronic allergic conditions (rhinitis, atopic dermatitis) and acute difficulties (anaphylaxis).